Peran Badan Penyelenggara Jaminan Produk Halal dalam Meningkatkatkan Kepercayaan Konsumen di Indonesia - Revalina Aurelia Oktanti; Azza Nuha Nisrina; Tina Syahadatina; M. Sarifuddin Hidayatullah; Ersya Faraby (CV. ITTC INDONESIA, 2025)
This research uncovers the significant role of the Halal Product Assurance Organizing Body (BPJPH) in fostering consumer trust within Indonesia’s massive Muslim-majority marketplace. The study zeroes in on the rising demand for halal certification, which has evolved into both a legal imperative and a valuable business asset, essential for upholding the rights of Muslim consumers as outlined in the constitution. By adopting a socio-legal approach and relying on library research, the study examines BPJPH’s specific roles in regulation, monitoring, and collaboration in halal product assurance (JPH). The findings show that halal certification is more than just a marker of compliance; it’s a multi-faceted tool that guarantees product integrity, cleanliness, and conformity to Islamic principles. It not only builds consumer trust but also drives loyalty and purchasing behavior, giving companies a competitive advantage in international markets. The rigorous oversight and consistent regulatory framework enforced by BPJPH are key to maintaining this trust and facilitating the growth of Indonesia’s halal industry.,